Implementing Azure Cloud Design Patterns : Implement efficient design patterns for data management, high availability, monitoring and other popular patterns on your Azure Cloud. - Demiliani, Stefano (Packt Publishing, 2018)
A well designed cloud infrastructure covers factors such as consistency, maintenance, simplified administration and development, and reusability. Hence it is important to choose the right architectural pattern as it has a huge impact on the quality of cloud-hosted services. This book covers all Azure design patterns and functionalities to help ...